„REFLECTION EFFECT” AS A THEORETICAL CONCEPT - Самброс, А.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The article deals with the concept of „reflection effect” as an important element of political marketing and of the theory of applied political sciences. The impact of marketing technologies on the development of the political process and the creation of political products are examined.